Drug‐loading three‐dimensional scaffolds based on hydroxyapatite‐sodium alginate for bone regeneration. Issue 2 (17th June 2020) - Liang, Tingting; Wu, Jingwen; Li, Fuyao; Huang, Zhu; Pi, Yixing; Miao, Guohou; Ren, Wen; Liu, Tiantao; Jiang, Qianzhou; Guo, Lvhua
Abstract: Bone tissue engineering is a promising approach for tackling clinical challenges. Osteoprogenitor cells, osteogenic factors, and osteoinductive/osteoconductive scaffolds are employed in bone tissue engineering. However, scaffold materials remain limited due to their source, low biocompatibility, and so on. In this study, a composite hydrogel scaffold composed of hydroxyapatite (HA) and sodium alginate (SA) was manufactured using three‐dimensional printing. Naringin (NG) and calcitonin‐gene‐related peptide (CGRP) were used as osteogenic factors in the fabrication of drug‐loaded scaffolds. Investigation using animal experiments, as well as scanning electron microscopy, cell counting kit‐8 testing, alkaline phosphatase staining, and alizarin red‐D staining of bone marrow mesenchymal stem cell culture showed that the three scaffolds displayed similar physicochemical properties and that the HA/SA/NG and HA/SA/CGRP scaffolds displayed better osteogenesis than that of the HA/SA scaffold. Thus, the HA/SA scaffold could be a biocompatible material with potential applications in bone regeneration. Meanwhile, NG and CGRP doping could result in better and more positive proliferation and differentiation.